WHAT ARE THE ROLES OF EDUCATIONAL ELECTRONIC TOOLS IN READING MOTIVATION? A LITERATURE REVIEW - Nurul Fitriyah Almunawaroh (Universitas Indo Global Mandiri, 2022)
Two main types of educational technology tools (ICT and DERs) are likely mediate and enhance reading motivation as well as reading comprehension through personalized activities and engaging activities. Though, technology provides students with various interactive features that can suit students’ learning style and learning level, framework and approaches like constructionist framework, top-down and bottom-up approaches, as well as learning from technology and learning with technology concepts will navigate learning activities on what ways and how the technologies are used in reading activities, thus improve students’ reading motivation, reading comprehension, and reading fluency. Reading motivation questionnaire alone might give insight to the researchers on the change of reading motivation before and after the intervention, but triangulating the data from questionnaire with the data from interview, observation, and students diary likely expands the information gauged in terms of students’ problems and difficulties in using the technologies, their preference regarding learning activities, and how the technologies with the approaches/concepts/approach can enhance learning, increase students’ reading motivation, comprehension, and fluency.